Using Capital Markets as Market Intelligence: Evidence from the Pharmaceutical Industry - Markovitch, Dmitri G.; Steckel, Joel H.; Yeung, Bernard (Management Science, 2005)
Financial theory posits that capital markets convey through stock prices their expectation of the firm’s future performance. We use concepts from principal-agent theory and prospect theory to provide a theoretical explanation for the role stock price variation plays in managerial decision making. We then empirically investigate what specific decisions managers undertake in response to stock price variation. We perform our empirical analyses in the context of the pharmaceutical industry. We find that drug firms whose stock underperformed the industry react differently than drug firms with high-performing stocks. Specifically, laggards tend to implement more changes to their current product portfolio and distribution than high-performing firms. The more laggards underperform, the more they implement acquisitions aimed to produce immediate improvement in the firm’s product portfolio. In contrast, drug firms whose stocks outperform the industry tend to make fewer changes to their current portfolio and distribution. Instead, they focus more on long-term research and development and marketing of existing products. We interpret these findings in light of industry key success factors.